M.I. DEMKOV ON THE PRINCIPLES OF EDUCATION - Aleksyeyeva, L.V. (Pedagogy of Higher and Secondary Education, 2004)
The author examines the views of M.I.Demkov, a representative of the national pedagogics at the end of the XIX c. Beginning of the rote, as for the process of upbringing.